Can ICT training change teachers' attitudes towards using technology in teaching? A perspective from a U.A.E high school - Badran, Basel.A.R. (2009)
This action research explores the effect of the provision of sustainable ICT training to teachers on changing their attitudes towards increased ICT use in teaching. The research also sought to identify barriers and enablers to ICT uptake at different levels. An ICT in-service training was offered to three government high school teachers who initially responded to an ICT competence audit. The teachers also responded to an ICT survey before and after the training. The instrument collected information on their level of ICT use, their attitudes and opinions towards technology use and finally their training experiences. Data from both surveys as well as interpretive observations and interviews during the 8 months of training were analysed and compared. Results suggest a positive shift in teacher's attitudes towards ICT training and ICT use in teaching. The study also identified three fundamental issues that greatly affect the teacher's attitudes towards technology and their degree of adoption and use of ICTs within UAE government schools; (a) sustainable in-service training, (b) access to ICTs, and (c) sustainable guidance and technical support.